OHP-002 Supply and demand: Reducing the time to complete the oral drug administration round. (14th February 2016) - Kieran, M; Cleary, M; Teeling, SP; Creed, M; Meegan, C
Abstract : Background: Drug prescribing and administration is one of the primary interventions for influencing patient health. 1 When interrupted once during drug administration, the risk of error increases by 12.7%. 2 In February 2013, nursing staff spent, on average, 135 min undertaking the 08.00 oral drugs round. Lean methodology has been successfully used in healthcare for process improvement so it was employed to review the timing and safety of the drug administration round. Purpose: To review the drug administration round using Lean methodology to: eliminate non-necessary steps; reduce the time taken; reduce interruptions; provide a safer environment. Material and methods: A surgical ward was the study ward. A 'process map' of the drug administration round was generated, with each step analysed for the value added. Areas for improvement were identified and rated in terms of impact and feasibility. The time taken to complete the 08.00 drug round and interruptions encountered were recorded 7 days pre-implementation, 3 weeks post-implementation and then at defined intervals for follow-up. Results: The improvements introduced as a result of Lean analysis were; a 'do not disturb' campaign to reduce interruptions; re-organisation of the drug trolley; checklist for preparing the drug trolley prior to rounds; use of a coloured flag to identify stocking requirements or any drug chart issues; and a standardised process to communicate stock requirements between pharmacy and nursing. The project was rolled out in May 2013, with re-audits in September 2013, July 2014 and November 2014. The average 08.00 drug round timing decreased by 63 min per day. The time variation for drug round completion decreased by 14 min per round. Total interruptions have increased from the baseline study. Ward clinical pharmacists indicated that the drug supply process has improved along with communication between nursing and pharmacy. Conclusion: Lean methodology was successfully employed to reduce the time taken to complete the oral drug administration round. Interruptions during drug administration have also reduced. This demonstrates that Lean methodology can increase efficiency and safety in the healthcare setting. References and/or Acknowledgements: Maxwell S, Walley T. Teaching safe and effective prescribing in UK medical schools: a core curriculum for tomorrow's doctors. Br J Clin Pharmacol 2003;55:496-503 Institute for Safe Medication Practices, Medication Safety Alert 2013;18(2) No conflict of interest.